Chemokine receptor CXCR7 antagonism ameliorates cardiac and renal fibrosis induced by mineralocorticoid excess - Bing H. Wang; Remy Robert; Francine Z. Marques; Niwanthi Rajapakse; Helen Kiriazis; Charles R. Mackay; David M. Kaye (Scientific Reports)
Abstract Cardiorenal fibrosis is a common feature of chronic cardiovascular disease and recent data suggests that cytokines and chemokines may also drive fibrosis. Here we tested the hypothesis that CXCR7, a highly conserved chemokine receptor, contributes to cardiac and renal fibrosis. We generated an anti-mouse CXCR7-specific monoclonal antibody (CXCR7 mAb) and tested its anti-fibrotic actions in cardiorenal fibrosis induced using the deoxycorticosterone acetate/uni-nephrectomy (DOCA-UNX) model. CXCR7 mAb treatment (10 mg/kg, twice weekly for 6 weeks) significantly attenuated the development of cardiac and renal fibrosis, and reduced fibrotic and inflammatory gene expression levels, in the absence of an effect on blood pressure. Immunohistochemical analysis demonstrated an increase in the vascular expression of CXCR7 in DOCA-UNX-treated mice. This study demonstrated that a CXCR7 mediated pathway plays a significant role in cardiac and renal fibrosis induced by DOCA-UNX treatment. Accordingly, antagonism of CXCR7 may provide a therapeutic opportunity to mitigate against fibrosis in the setting of mineralocorticoid excess.